2018
DOI: 10.1038/s41388-018-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells enhance human breast cancer growth and cancer stem cell-like properties through adipsin

Abstract: Tumor microenvironment plays a key role for tumor development and progression. Although adipose tissue is a predominant component of stroma in mammary tissues and secretes various cytokines, chemokines and growth factors, roles of adipocytes in breast cancers remain to be elucidated. In this study, we found that adipsin, an adipokine secreted from mammary adipose tissues, enhanced proliferation and cancer stem cell (CSC)-like properties of human breast cancer patient-derived xenograft (PDX) cells. Adipsin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 53 publications
2
97
1
2
Order By: Relevance
“…To analyze the expression levels of mRNAs, RNA samples were reverse transcribed using a High Capacity cDNA Reverse Transcription Kit (Life Technologies). Semiquantitative PCR was undertaken as described previously 23 . The sequences of primers used are presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the expression levels of mRNAs, RNA samples were reverse transcribed using a High Capacity cDNA Reverse Transcription Kit (Life Technologies). Semiquantitative PCR was undertaken as described previously 23 . The sequences of primers used are presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, accumulating evidence suggests that tumor progression and metastasis are not only affected by biological behaviors of cancer cells but also by tumor microenvironments (TMEs), which are defined as the bidirectional interactions between tumor cells, stromal cells, and cellular elements [10,11]. Tumor stroma, as an important component of TME, promotes tumor progression through production of various nutrition, growth factors, chemokines, and cytokines [12][13][14]. As a result, the tumor-stromal ratio (TSR), a new parameter that represents the proportion of tumor-associated stroma, was introduced to the field of cancer research [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the survival rate, growth, and invasiveness of tumors after interacting with ASCs, which are CAAs components. By excreting a variety of bioactive factors including visfatin, adipsin, CCL5, IGF, HGF, VEGF, IL-8, and TGF-β, ASCs can exert biological influences on proliferation, epithelial-mesenchymal transition, and metastasis ( Huang et al, 2019 ; Goto et al, 2019 ). ASCs could differentiate into cancer-associated fibroblasts in breast cancer environment, especially with a more pronounced effect on obese patients ( Cho et al, 2012 ; Ecker et al, 2019 ).…”
Section: Asc-exos In Breast Cancer and Breast Reconstructionmentioning
confidence: 99%